The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/cbdv.201800148
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Constituents ofJuniperus turbinataGuss. from La Maddalena Archipelago

Abstract: A comprehensive phytochemical study of Juniperus turbinata (Cupressaceae) collected from La Maddalena Archipelago (Sardinia, Italy) is reported. Both the essential oil and the ethanolic extract obtained from the aerial parts were analyzed. The essential oil appears to belong to a new chemotype compared to other Mediterranean juniper accessions, as it was favored by geographic isolation of the isles. It showed a low content of monoterpene hydrocarbons and α-terpineol, ent-manoyl oxide, 1,10-di-epi-cubenol as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…In some cases the chemotaxonomic relevance has also been demonstrated. In gymnosperms, apigenin derivatives are mostly present in dimeric forms, with apigenin residues variously coupled, e.g., with C‒C linkage as in cupressuflavone and amentoflavone (I-8, II-8″ and I-3′, II-8″, respectively), or C‒O linkage (I-4′, II-6″) as in hinokiflavone (Figure 2) [24,25,26,27]. Biogenetically, apigenin is a product of the phenylpropanoid pathway and may be obtained from both phenylalanine and tyrosine, two shikimate-derived precursors.…”
Section: Apigenin Chemistrymentioning
confidence: 99%
“…In some cases the chemotaxonomic relevance has also been demonstrated. In gymnosperms, apigenin derivatives are mostly present in dimeric forms, with apigenin residues variously coupled, e.g., with C‒C linkage as in cupressuflavone and amentoflavone (I-8, II-8″ and I-3′, II-8″, respectively), or C‒O linkage (I-4′, II-6″) as in hinokiflavone (Figure 2) [24,25,26,27]. Biogenetically, apigenin is a product of the phenylpropanoid pathway and may be obtained from both phenylalanine and tyrosine, two shikimate-derived precursors.…”
Section: Apigenin Chemistrymentioning
confidence: 99%
“…Juniperus turbinata Guss.) ethanol extract showed the strongest cytotoxic activity (IC 50 values of 0.06, 0.114, and 0.201 μM on human colon cancer HCT116, human malignant melanoma A375, and human breast adenocarcinoma MDA-MB-231 cell lines, respectively), being several times more potent than the reference compound cisplatin (IC 50 values of 1.87 to 11.86 μM) [ 19 ] indicating that imbricataloic acid make a promising anticancer drug candidate.…”
Section: Introductionmentioning
confidence: 99%
“…Juniperus turbinata Guss.) exhibits cytotoxic effects against HCT116, A375, and MDA-MB-231 human tumor cell lines, in a concentration-dependent inhibitory effect with IC 50 values of 9.48–33.69 μg/mL [ 19 ]. Juniperus oxycedrus essential oil exhibited high antitrypanosomal activity (IC 50 of 0.9 μg/mL) against Trypanosoma brucei brucei , with no cytotoxic effects on RAW 267.4 macrophage cell line showing the highest selectivity index (63.4) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cupressoflavone ( 1 ) was previously reported from Juniperus turbinate (Venditti et al, ), and it was shown to possess cytotoxic activity against the human cancer cell lines breast adenocarcinoma (MDA‐MB 231), malignant melanoma (A375), and colon carcinoma (HCT116), with IC 50 values of 16.1, 12.7, and 19.3 μM, respectively, after 72 hr incubation using the MTT assay. However, on the present study, compound 1 displayed a significant decrease in the percentage viability of lung cancer cells A549 at concentrations higher than 0.33 μM (Table ).…”
Section: Resultsmentioning
confidence: 99%